Creative Writing for Social Research : A Practical Guide - Phillips, Richard (Book collections on Project MUSE., 2021)
Inviting beginners and more experienced researchers to explore new ways of writing, this book introduces readers to creatively written research in a variety of formats including plays and poems, videos and comics. It not only gives social researchers permission, but also shows them how, to write creatively.